Diagnóstico da qualidade da água da microbacia do Córrego da Aldeia em Fernandópolis-SP - Capanema, Gilberto Alves [UNESP] (2015)
Drinking water is a resource that is becoming increasingly scarce on the planet, meanwhile the world population is increasing, which ultimately could cause a big problem of world order. In addition, the man has occupied so increasingly disorderly watersheds through deforestation activities, fires, harmful agricultural practices, aggressive extractive activities, widespread urban occupations generating soil sealing, release of industrial and domestic sewage into rivers and lakes. Anyway, all these actions impacting the environment have generated a deterioration of quality of natural waters, with risk of spread of waterborne diseases to human being. The assessment of water quality can support the formulation of management plans and management of aquatic systems. In this work, the quality of the water stream village, in the municipality of Fernandópolis-SP, was assessed using the Water Quality Index (WQI) and its state of degradation associated with the use of the surrounding area. Water sampling and the implementation of socio-economic and environmental questionnaire were conducted between September/2013 and August/2014 in five sampling sites and in the surrounding area streams. The samples were analyzed for physical, chemical and microbiological parameters. It was found that during the rainy season there was a fall in the value of the IQA, because of the increased turbidity and total solids in the water, from the carrying of solid particles by runoff, indicating lack of soil conservation practices and forest riparian. Water quality ranged from fair to good in the period under study, where some parameters exceeded or fallen below the limits established by CONAMA Resolution n o 357/05 to water bodies class II. In some places, due to the form of land use, watershed presented the environmental fragility with potential risk of contamination of their water resources, and the lack of information and awareness of residents about the environmental...